Attentional control associated with core cognitive maintenance factors of social anxiety. Issue 4 (25th September 2018) - Sluis, Rachel A.; Boschen, Mark J.; Neumann, David L.; Murphy, Karen
Models of social anxiety emphasize anticipatory processing (AP) and post-event processing (PEP) as repetitive negative thinking (RNT) processes that occur before and after social-evaluative events, respectively. Both AP and PEP have been implicated as maladaptive processes which maintain social anxiety. Accordingly, a common vulnerability, such as poor attentional control, may serve to maintain both. The present research included two separate samples to investigate the relationship between attentional control and AP (Sample 1) and PEP (Sample 2). Participants ( n = 49 for Sample 1; n = 35 for Sample 2) completed self-report measures of social anxiety, AP or PEP, attentional control, and trait anxiety. Poorer total attentional control was associated with social anxiety in both samples. In addition, attentional control total and attentional shifting were negatively associated with PEP (Sample 2) but not with AP (Sample 1). Mediation modeling suggested that trait anxiety mediated the relationship between total attentional control and PEP. The findings suggest that attentional control plays a role in the regulation of emotion, such as anxiety, and RNT processes, such as PEP, but not AP.